Evaluación Del Barbasco (Deguelia Utilis) En El Control De Pulgas En Caninos En Una Fundación De Bogotá (2022)
The barbasco or cube (Deguelia utilis) widely distributed throughout Latin America, belongs to the legume family, its main compound being rotenone, which is a toxic substance obtained from its roots. Traditionally, its main compound is used to control crop pests